2015
DOI: 10.1590/s1679-45082015ao2878
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity as a protective factor for development of non-alcoholic fatty liver in men

Abstract: Objective To determine the impact of physical activity on the prevalence of fatty liver, metabolic and cardiovascular disease in adult men.Methods This study evaluated 1,399 men (40.7±8.18 years) with body mass index of 26.7kg/m2 (±3.4) who participated in the Protocol of Preventive Health Check-up at Hospital Israelita Albert Einstein from January to October 2011. We conducted tests of serum blood glucose, total cholesterol, LDL, HDL, triglycerides, reactive c-protein, aspartate transaminase, alanine transami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
0
7
0
6
Order By: Relevance
“…It has, from this perspective, been argued that MetS manifestation is a consequence of high carbohydrate intake, as it attenuates high fasting glucose levels, triggers insulin secretion, contributes to high plasma triglycerides, attenuates the HDL proportion and supports high blood pressure (Volek and Feinman, 2005 ; Westman et al, 2007 ). A further transitional state toward MetS is seen in the development of a fatty liver disease (NAFLD), including dyslipidaemia, associated with sedentary life style and lack of physical exercise (Pinto et al, 2015 ). High carbohydrate intake is typically associated with microbiotic fermentation of nondigestible polysaccharides, which are transformed into better manageable short chain fatty acids (SFCAs, acetate, propionate, and butyrate) that, however, increase reactive oxygen species (ROS), pro-inflammatory cytokines, decrease gut membrane integrity, and induce epigenetic modifications via inhibition of histone deacetylases, thus reducing respective gene expression (Tan et al, 2014 ).…”
Section: Traditional Hypotheses On Aetiopathologymentioning
confidence: 99%
“…It has, from this perspective, been argued that MetS manifestation is a consequence of high carbohydrate intake, as it attenuates high fasting glucose levels, triggers insulin secretion, contributes to high plasma triglycerides, attenuates the HDL proportion and supports high blood pressure (Volek and Feinman, 2005 ; Westman et al, 2007 ). A further transitional state toward MetS is seen in the development of a fatty liver disease (NAFLD), including dyslipidaemia, associated with sedentary life style and lack of physical exercise (Pinto et al, 2015 ). High carbohydrate intake is typically associated with microbiotic fermentation of nondigestible polysaccharides, which are transformed into better manageable short chain fatty acids (SFCAs, acetate, propionate, and butyrate) that, however, increase reactive oxygen species (ROS), pro-inflammatory cytokines, decrease gut membrane integrity, and induce epigenetic modifications via inhibition of histone deacetylases, thus reducing respective gene expression (Tan et al, 2014 ).…”
Section: Traditional Hypotheses On Aetiopathologymentioning
confidence: 99%
“…Emerging research provides suggestive evidence that regular participation in physical activity (PA) may help to prevent against liver disease ( Ryu et al, 2015 , Berzigotti and Saran, 2015 , Whitsett and VanWagner, 2015 , Keating et al, 2015 , Pinto et al, 2015 , Hallsworth et al, 2015 ). The most common cause of liver disease in the United States is a spectrum of liver conditions known collectively as non-alcoholic fatty liver disease (NAFLD).…”
Section: Introductionmentioning
confidence: 99%
“…Although there were significant changes in many variables, the changes did not lead to a desirable point. Pinto et al noted significant decrease in BM, HDL and TG levels in active males with fatty liver (12). Also Khaoshbaten showed significant decrease of lipid profiles after three months of aerobic exercise (22).…”
Section: Discussionmentioning
confidence: 99%
“…Be-sides overweight, alanine aminotransferase (ALT) and aspartate aminotransferase are markers of liver dysfunction (11). Studies suggested that the fatty liver metabolic parameters could improve by lifestyle modification by increasing physical activity and changing bad eating habits (12,13); therefore the relationship between physical activity (PA) and liver enzyme levels aspartate aminotransferase (AST) and AST/ALT are shown (11,14). Haus et al noted that shortterm exercise reduces the risk of NAFLD progression by improving the hepatic lipid profiles (15).…”
Section: Introductionmentioning
confidence: 99%